Narrowing development gaps in ASEAN - Alavi, Rokiah; Ramadan, Aisha (SESRIC, 2008)
Development gaps happen when there is a difference in either the per capita income or other social development between countries or regions. The enlargement process in the ASEAN widened further the existing developmental gap. Using GDP per capita, HDI index and information technology data, this paper examines the extent of the developmental gap in the ASEAN prior to the enlargement exercise and after the process. The paper also examines income convergence in the ASEAN over the period 1970-2003. The results reveal that income gap among the ASEAN members did not converge after decades of integration process. Comparison with the EU's integration experience shows that the structural funds and other policy tools executed by the EU are among the key elements of convergence that are absent in the ASEAN. Political will in ensuring compliance and effective implementation is clearly needed for a successful ASEAN economic integration.